2018
DOI: 10.1101/462424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Time Course of Ineffective Sham Blinding During 1mA tDCS

Abstract: Background: Studies using transcranial direct current stimulation (tDCS) typically compare the effects of an active (10-30min) relative to a shorter sham (placebo) protocol. Both active and sham tDCS are presumed to be perceptually identical on the scalp, and thus represent an effective method of delivering double-blinded experimental designs. However, participants often show above-chance accuracy when asked which condition involved active/sham retrospectively.Objective/Hypothesis: We aimed to assess the time … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…One important difference is the duration of the real tDCS: Whereas in our study it was 20 min, Greinacher et al. () used 10 min. Blinding efficacy of FSF protocols seems to be better for real tDCS protocols with shorter stimulation durations (e.g., 10 min).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…One important difference is the duration of the real tDCS: Whereas in our study it was 20 min, Greinacher et al. () used 10 min. Blinding efficacy of FSF protocols seems to be better for real tDCS protocols with shorter stimulation durations (e.g., 10 min).…”
Section: Discussionmentioning
confidence: 77%
“…The stimulation parameters used in this study were similar to the ones reported here: Both used 1 mA tDCS, comparable electrode montage and a FSF protocol (with identical fade-in/out periods and similar shortstimulation periods: 15 vs. 20 s). One important difference is the duration of the real tDCS: Whereas in our study it was 20 min, Greinacher et al (2018) used 10 min. Blinding efficacy of FSF protocols seems to be better for real tDCS protocols with shorter stimulation durations (e.g., 10 min).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations